Spectral reflectance of atmospheric dust as an indirect indicator of its soil origin - I. Yu. Savin; G. V. Vindeker; O. O. Plotnikova; A. Yu. Romanovskaya (Бюллетень Почвенного института им. В.В. Докучаева, 2023)
Atmospheric dust affects both human health and climate change. Therefore, the study of atmospheric dust is one of the important tasks of many scientific fields. The aim of our research was to indirectly assess the relation of atmospheric dust over arable lands of two test sites in Tver and Tula regions of Russia with soils. Dust was analyzed on aspirator filters after pumping specified volumes of air at the level of 20–30 cm above the arable surface. Its spectral reflectance was used as a criterion of soil origin of dust, which was compared with the reflectance of the size fraction (50–200 nm) of soils isolated by dry sieving of a sample of arable soil horizon. The spectral reflectance of dust was calculated based on approaches of linear separation of spectral mixture, taking into account the projective coverage of dust particles on filters, which was determined by analyzing microscope photographs of the filters in GIS. As a result, it was found that the recovered dust spectra on the filters correlate well with the spectra of the same size soil fraction separated by dry sieving, which indirectly confirms the predominance of specifically soil dust on the filters. Spearman correlation coefficient is within the range of 0.84–0.90, Kendall's Tau correlation coefficient varies within 0.70–0.79 (at significance level p < 0.05). Under the conditions of insignificant atmospheric dust load and when collecting a sufficient amount of dust for direct analysis is time and labour consuming, the approach used may serve as an alternative for indirect confirmation of the soil origin of dust in the near ground layer of the atmosphere. In the future, this approach can be used as a basis for monitoring of arable soils deflation.